Linkages between ozone-depleting substances, tropospheric oxidation and aerosols - A. Voulgarakis; D. T. Shindell; G. Faluvegi (Atmospheric Chemistry and Physics, 2013)
Coupling between the stratosphere and the troposphere allows changes in stratospheric ozone abundances to affect tropospheric chemistry. Large-scale effects from such changes on chemically produced tropospheric aerosols have not been systematically examined in past studies. We use a composition-climate model to investigate potential past and future impacts of changes in stratospheric ozone depleting substances (ODS) on tropospheric oxidants and sulfate aerosols. In most experiments, we find significant responses in tropospheric photolysis and oxidants, with small but significant effects on methane radiative forcing. The response of sulfate aerosols is sizeable when examining the effect of increasing future nitrous oxide (N2O) emissions. We also find that without the regulation of chlorofluorocarbons (CFCs) through the Montreal Protocol, sulfate aerosols could have increased by 2050 by a comparable amount to the decreases predicted due to relatively stringent sulfur emissions controls. The individual historical radiative forcings of CFCs and N2O through their indirect effects on methane (−22.6 mW m−2 for CFCs and −6.7 mW m−2 for N2O) and sulfate aerosols (−3.0 mW m−2 for CFCs and +6.5 mW m−2 for N2O when considering the direct aerosol effect) discussed here are non-negligible when compared to known historical ODS forcing. Our results stress the importance of accounting for stratosphere-troposphere, gas-aerosol and composition-climate interactions when investigating the effects of changing emissions on atmospheric composition and climate.